Proses Pengolahan dan Pemurnian Bijih Tembaga dengan Cara Konvensional dan Biomining - Anton Sudiyanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Indonesia has ore reserves of copper (Cu) which is very large, most of the reserves with porphyry Cu content in the ore vary between 0.1 - 2%. In addition to Cu, usually ore associated with other metals such as gold (A), silver (Ag) and rare metals such as Palladium (Pd ), Selenium ( Se ) and others. Several types of Cu ore there is Bornite (Cu5FeS4), Calcopyrite (CuFeS2), Covellite (CuS) with some impurities such as pyrite (FeS2), Magnetite (Fe3O4), hematite (Fe2O3), or Quartz (SiO2). Caused most of the sulfide minerals in the conventional treatment (physical - chemical ) would be more effective if the initial process is " concentrating "using flotation and gravity if it is in many ores of gold (Au) in the form of Native. Furthermore, conventional purification process using Pyro way Metallurgy, Metallurgy and Electro Hydro Metallurgy. Biomining mineral extraction using bacteria. Definition biomining intact is the process of extracting valuable minerals from ore or tailings from mining rest with the help of microorganisms , especially bacteria. Biomining process copper ore by leaching microbial -based reaction that uses bacteria Acidithiobacillus ferrooxidans biomining is an effective technology and environmentally friendly which can be used for purification of ore and precious metals in concentrate.